1980
DOI: 10.1258/002367780781071166
|View full text |Cite
|
Sign up to set email alerts
|

Calcification in the adrenals and ovaries of monkeys

Abstract: 363Summary Adrenal calcification occurred in 52·6% of rhesus monkeys, 4· 7% of cynomolgus monkeys and 2·4'% of baboons examined. In contrast, ovarian calcification was observed in 62·3% of baboons, 38'J{, of cynomolgus and 22·3% of rhesus monkeys examined.Calcification occurs commonly in devitalized tissues. The incidence shows considerable species ditTerences. Ross, Gainer & Innes (1955) (1974) and Ishmael (1975).During routine toxicological investigations, differences were observed in the incidences of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Focal mineral deposits were observed in 50% of the animals (approximately equal numbers of control and experimental), a common histological finding in adult rhesus monkeys [31], [32] and baboons [33]. A single incidental focus of fibrosis was detected in the medulla of a 6-OHDA-treated animal; no other significant lesions were observed in the adrenal medulla (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 90%
“…Focal mineral deposits were observed in 50% of the animals (approximately equal numbers of control and experimental), a common histological finding in adult rhesus monkeys [31], [32] and baboons [33]. A single incidental focus of fibrosis was detected in the medulla of a 6-OHDA-treated animal; no other significant lesions were observed in the adrenal medulla (Figure 2A,B).…”
Section: Resultsmentioning
confidence: 90%
“…The findings in this study were generally consistent with the incidence and occurrence of similar lesions described in the literature. These findings include gastritis (Drevon-Gaillot et al 2006; Scott 1999), interstitial nephritis (Bennet et al 1998; Drevon-Gaillot et al 2006), inflammatory lesions of the heart (Chamanza et al 2006; Drevon-Gaillot et al 2006; Keenan and Vidal 2006), inflammatory cell infiltrations in the liver (Foster 2005; Ito et al 1992), tension lipidosis of the liver (Drevon-Gaillot et al 2006), mineralization in the adrenal gland (Kast et al 1994; Majeed and Gopinath 1980), pneumoconiosis in the lungs, pigment in the lamina propria of the small intestine (Drevon-Gaillot et al 2006; Scott 1999), and lung findings associated with continuous intravenous infusion (Lilbert and Burnett 2003). In addition, a well-presented and extensive review of incidental findings and nonlesions in primates and their possible etiologies has also been published (Lowenstine 2003), and most of the findings discussed in this particular paper were evident in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Laminated calcium deposits among primary follicles in ovaries are well-known findings in rhesus monkeys and occur in about 40% of the animals according to our studies reported with the strain. Ovarian calcification has been observed in 62-81 % of baboons, 38% of cynomolgus and 22% of rhesus monkeys (Ishmael 1975, Majeed & Gopinath 1980. The finding is said to disappear together with the shrinking number of primary follicles.…”
Section: Discussionmentioning
confidence: 99%
“…An impressive picture of the lesions in their final stage has been shown by Liebegott (1958), courtesy of Lund (1956l. The incidence of the finding in 3 monkey species has been compared by Majeed and Gopinath (1980). The aetiology and pathogenesis of adrenal calcinosis in monkeys have not yet been established, but stress has been suggested as a disposing factor (Skelton-Stroud and Ishmael 1985).…”
mentioning
confidence: 99%